Studies on Flowering Behavior and Seed Characteristics of Dendrocalamus giganteus - Jalil, Parvez; Shukla, P. K. (Indian Forester, 2010)
A peculiar phenomenon, after flowering has been observed in Dendrocalamus giganteus. After flowering in February, 2005, the clumps continued its growth through emergence of new clumps till 2008. The average seed weight per clump was 55.53Â±6.21 mg and average germination was 53 per cent. The fruit/seed setting was very poor.